Analysis of Environmental Factors and Parenting of Pregnant Women on the Development of Stunted Children - Sri Agus Setyaningsih, Tunggul; Wahyuni, Hesti; Ratnasari, Fithri; ., Irwanto (Oshada, 2025)
Stunting is a chronic nutritional problem influenced by environmental factors and parenting patterns starting during pregnancy. This study aims to analyze the relationship between environmental factors and maternal parenting patterns and the incidence of stunting in children in Gunungkidul Regency. This quantitative study used a case-control design with a sample of 210 mothers with children aged 24–59 months. Data were collected through structured interviews, home observations, and medical records of pregnancy examinations. The variables studied included antenatal care (ANC) compliance, home sanitation, nutritional intake during pregnancy, housing density, and access to clean water. Data analysis was performed using the Chi-Square test and logistic regression with a significance level of p<0.05. The results of the analysis showed that low ANC compliance (OR=3.11; 95% CI: 1.21–8.01; p=0.013), poor home sanitation (OR=2.75; 95% CI: 1.18–6.38; p=0.019), and poor nutritional intake of pregnant women (OR=2.42; 95% CI: 1.03–5.66; p=0.043) were the dominant factors significantly associated with stunting. Meanwhile, access to clean water and housing density showed a weaker relationship. The conclusion of this study is that increasing ANC compliance, improving household sanitation, and fulfilling nutritional needs of pregnant women are key strategies for preventing stunting in Gunungkidul. Integrated interventions from pregnancy are needed to break the cycle of stunting between generations.